The Influence of Fairness in Distribution, Procedural and Interactional Justice on Employee Performance in Contractor Company - Dian Aryono, Muhamad; Marisi (Management Research Studies Journal, 2024)
A competent workforce is needed to achieve the company's goals and mission. Companies need to create responses to foster and improve employee performance. Based on the phenomenon in the field, there is a distributive justice gap in the contractor company environment, precisely in the Manyar Maju Refinery (MMR) project. The research is based on the comparison of salaries and benefits received by employees at the same grade. In addition, the balance of procedural justice and interactional justice is also questioned. The purpose of the study is to explain the effect of organizational justice on employee performance. This research design is causal research. Research variables include independent variables and dependent variables. The independent variables are distributive justice, procedural justice, and interactional justice. While the dependent variable is employee performance. The research population is all employees of the contractor company who work on the MMR project as many as 986 employees. The number of research samples was 285 samples and the sampling technique used quota sampling. Data collection techniques using questionnaires, and variable measurements using questionnaire measuring instruments. Data analysis techniques using multiple linear regression analysis. The results of this study indicate that distributive justice does not affect employee performance. Procedural justice has a positive effect on employee performance. Interactional justice has a positive effect on employee performance. Distributive justice, procedural justice, and interactional justice are jointly proven to affect employee performance in MMR projects.